DEVELOPMENT OF STATIC FLUID LEARNING PROPS TO IMPROVE STUDENTS’ ARGUMENTATION SKILLS - Iwan, Muhammad; Suyatna, Agus; Warsito (International Journal of Research -GRANTHAALAYAH, 2018)
This study aims to develop static fluid material props in an effort to improve students’ argumentation skills. Design development using 4-D development model consists of four stages, namely Define, Design, Development, and Disseminate. The test subjects of this study were 5 physics teachers and 75 students from three high schools in Bandar Lampung. Data were collected through observation in the preliminary study, questionnaires to see the responses of students, teachers, and experts on the developed aids and tests of the method of one pretest and posttest design. The questionnaire data were analyzed using scoring techniques and improved learning outcomes using the N-gain formula. According to the response of students and teachers there is a clear U-shaped hose that contains water that can be observed movement, there are sensors and LED lights that can live when the movement of water through the sensor. The second props are simple hydraulics to prove Pascal’s law by laying loads of different weight on both sides of the piston with different cross-sectional areas. An effective tool for improving student learning outcomes and argument skills involves making claims and warrants, effective enough to improve the skills of backing, but less effectively to improve rendering skills.